An Optoelectronic Switch Based on Intrinsic Dual Schottky Diodes in Ambipolar MoSe2 Field‐Effect Transistors. (26th October 2015) - Pradhan, Nihar R.; Lu, Zhengguang; Rhodes, Daniel; Smirnov, Dmitry; Manousakis, Efstratios; Balicas, Luis
Abstract : The observation of a previously unreported optoelectronic effect, namely, a light‐induced diode‐like response in multilayered MoSe2 field‐effect transistors is reported. It has a sense of current rectification that is controllable through a gate voltage. It is argued, using numerical simulations, that this behavior results from the difference in the size of the Schottky barriers between the drain and source metal contacts. Each barrier can be modeled as a Schottky diode but with opposite senses of current rectification between them, with the diode response resulting from the light induced promotion of photogenerated carriers across the smaller barrier. The back gate voltage controls the sense of current rectification by modulating the relative amplitude between them. This effect, which gives rise to a novel type of optoelectronic switch, also yields a photovoltaic response. Hence, it can provide an alternative to p–n junctions when harvesting photovoltaic currents from transition metal dichalcogenides. It is argued that the photovoltaic efficiency associated to this effect can be increased by just increasing the relative asymmetry between both Schottky barriers. It is also suggested that this new electro‐optical effect has potential for technological applications. Abstract : It is demonstrated that the Schottky barriers between metallic interconnects and a van der Waals coupled semiconductor can lead to a new functionality, namely, a light‐induced diode‐like response with a sense of current rectification that can be controlled via a back gate voltage. This effect corresponds to a novel type of optoelectronic switch with a potential for technological applications.